On the statistics of crime arising from or connected with drunkenness, as indicating the importance of increasing the punishment of habitual drunkards, and of those who seriously injure their children by what they spend on drink - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1879)
In the discharge of my duty of reporting on criminal statistics in Ireland, some statistics have come under my notice which raise important questions as to the adequacy of the existing punishments for drunkenness.
Read at the Section of Economic Science and Statistics of the British Association, at Plymouth, August, 1877
Keywords: Drunkenness; Crime; Alcohol abuse; 314.15